Radiolysis of phenylalanine in solution with Bragg-Peak energy protons. (September 2018) - Ludwig, N.; Kusumoto, T.; Galindo, C.; Peaupardin, P.; Pin, S.; Renault, J.-P.; Muller, D.; Yamauchi, T.; Kodaira, S.; Barillon, R.; Raffy, Q.
Abstract: Phenylalanine aqueous solutions were irradiated with Bragg-Peak energy protons (0.6–5.6 MeV). An innovative circulation setup has been developed for the irradiation of these solutions with low-energy protons. Every detectable radiolysis product has been identified and quantified after irradiation. While tyrosines are well-known products of phenylalanine radiolysis, 2, 5-dihydroxyphenylalanine and dimers were detected in high quantities, for the first time. The track-yields (G'-values) of all products formed under proton irradiation were determined and compared to those obtained with gamma-rays, and 2, 5-dopa and dimers production seems to be specific to accelerated ions. A bi-radical mechanism could explain their higher production with a higher density of energy deposition in the track structure. Highlights: An innovative setup is presented for the irradiation of solution with low-energy ions. All phenylalanine radiolysis products under proton irradiations were identified and quantified. The possibility that some products are ion-specific is.